Heat capacity studies of magnetic phase transition in sodium-rich NaxCoO2 (0.73 ≤ x ≤ 0.87) - Baran, A.; Botko, M.; Zorkovská, A.; Kajňaková, M.; Šebek, J.; Šantavá, E.; Peng, J.P.; Lin, C.T.; Feher, A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2009)
Specific heat measurements in the temperature region from 2 to 50 K in magnetic field up to 10 T, orientedparallel and perpendicularly to the CoO2 layers were carried out on a series of high-quality single-crystals of NaxCoO2 (x = 0.73, 0.76, 0.77, 0.78 and 0.87). Surprisingly, sharp lambda type anomaly was observed only for the concentration x = 0.76 at temperature (21.80 ± 0.02) K, for all the remaining doping levels round anomaly in experimental data was visible at temperature ~ 20 K, indicating a smeared magnetic phase transition. While the magnetic field oriented perpendicularly to the CoO2 layers shifts the temperature of this anomaly to lower values, parallel magnetic field has no influence on it, what indirectly supports the idea of A-type antiferromagnetic ordering in studied systems.